Class Management Strategies In Increasing Achievement Study - Nur Wahyuni; Muhammad Dekar; Siti Mutiah (Outline Publisher, 2024)
Education is an important part for humans, if someone gets an education they will be able to develop the potential and talents that exist within them. The purpose of education is not only aimed at making someone literate, knowledgeable, or looking for a job. Learning activities affect the development and mindset of students, to achieve educational goals, teachers must be able to organize and manage classes so as to create a learning environment that allows students to learn well. This research uses the method of literature study. The research results are based on data from each article, the topic of which is classroom management strategies in improving learning achievement. As a class manager, the teacher has a strategic role including planning and carrying out activities with subjects and objects being students, determining and making decisions about strategies to be used for various activities, and providing alternative solutions to class problems and difficulties, cooperation skills are very important in education, both inside and outside of school. In explaining learning material, the teacher's voice must be in intonation, volume, pitch, and speed.